An eco-friendly and efficient trigeneration system for dual-fuel marine engine considering heat storage and energy deployment. (15th January 2022) - Yang, Liu; Su, Zixiang
Abstract: Under the background of energy and environmental crisis, to achieve energy-conservation and emission-reduction, we urgently need efficient and sustainable technologies to improve the energy efficiency and reduce emissions of the shipping industry. For this purpose, an eco-friendly and efficient trigeneration system is proposed. Initially, the mathematical model of the trigeneration system is established, and the fidelity is verified by comparing with the relevant investigation. Subsequently, the influence of fluid types and sensitivity parameters on the performance is discussed. Then, the conversion factor is introduced to quantify the contribution of each subsystem to the trigeneration system, and the optimal design parameters are obtained through the three-objective optimization. After determining the optimal design parameters, the change rule of the performance under working conditions is analyzed. Ultimately, the positive effect of heat storage and energy deployment characteristics in accumulator on dynamic-energy-demand is explored. The calculation results present that the power, thermal-efficiency, exergy-efficiency, the emission-reduction of the system, under the maximum working condition, reach 347.08 kW, 23.65%, 49.29% and 2210.04 t/year, and the recovery-time is only 7.35 years. The results prove that the system not only has excellent thermodynamic performance, economic and environmental benefits, but also can meet the dynamic-energy-demand of the marine. It provides theoretical guidance for researchers who are committed to overcoming the low-efficiency of waste-heat utilization, and brings enlightenment to enterprises for the research and innovation of waste heat recovery technology. Graphical abstract: Image 1 Highlights: An eco-friendly and efficient trigeneration system for marine engine is proposed. Multiforms of medium-low grade waste heat cascade recovery and utilization. A conversion factor is introduced to quantify the subsystem contribution. The optimal design parameters are determined by three-objective optimization. The remaining energy is stored and redeployed by accumulator to cope with dynamic demand.